Breast Implant–associated Anaplastic Large Cell Lymphoma: Updated Results from a Structured Expert Consultation Process - Benjamin Kim, MD, MPhil; Zachary S. Predmore, BA; Soeren Mattke, MD, DSc; Kristin van Busum, MPA; Courtney A. Gidengil, MD, MPH (Plastic and Reconstructive Surgery, Global Open, 2015)
Background: Despite increased cases published on breast implant–associated anaplastic large cell lymphoma (BIA-ALCL), important clinical issues remain unanswered. We conducted a second structured expert consultation process to rate statements related to the diagnosis, management, and surveillance of this disease, based on their interpretation of published evidence. Methods: A multidisciplinary panel of 12 experts was selected based on nominations from national specialty societies, academic department heads, and recognized researchers in the United States. Results: Panelists agreed that (1) this disease should be called “BIA-ALCL”; (2) late seromas occurring >1 year after breast implantation should be evaluated via ultrasound, and if a seroma is present, the fluid should be aspirated and sent for culture, cytology, flow cytometry, and cell block to an experienced hematopathologist; (3) surgical removal of the affected implant and capsule (as completely as possible) should occur, which is sufficient to eradicate capsule-confined BIA-ALCL; (4) surveillance should consist of clinical follow-up at least every 6 months for at least 5 years and breast ultrasound yearly for at least 2 years; and (5) BIA-ALCL is generally a biologically indolent disease with a good prognosis, unless it extends beyond the capsule and/or presents as a mass. They firmly disagreed with statements that chemotherapy and radiation therapy should be given to all patients with BIA-ALCL. Conclusions: Our assessment yielded consistent results on a number of key, incompletely addressed issues regarding BIA-ALCL, but additional research is needed to support these statement ratings and enhance our understanding of the biology, treatment, and outcomes associated with this disease.